1987
DOI: 10.1093/nar/15.17.7091
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of methylated CCCGGG sequences containing either N4-methylcytosine or 5-methytcytosine with Mspl, Hpall, Smal, Xmal and Cfr9I restriction endonudeases

Abstract: The cleavage specificity of R.Cfr9I was determined to be C decreases CCGGG whereas the methylation specificity of M.Cfr9I was C4mCCGGG. The action of MspI, HpaII, SmaI, XmaI and Cfr9I restriction endonucleases on an unmethylated parent d(GGACCCGGGTCC) dodecanucleotide duplex and a set of oligonucleotide duplexes, containing all possible substitutions of either 4mC or 5mC for C in the CCCGGG sequence, was investigated. It was found that 4mC methylation, in contrast to 5mC, renders the CCCGGG site resistant to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 17 publications
4
47
1
1
Order By: Relevance
“…In consideration of the possibility that the observed differences were due to the ability of MspI to cleave unmethylated DNA more efficiently than methylated DNA, naked genomic DNA from methylated and unmethylated transgenic liver was digested with increasing amounts of MspI under conditions nearly identical to those used with the nuclei. We observed MspI to cleave unmethylated sequences approximately twice as efficiently as methylated sequences (data not shown), in close agreement with the results of Butkus et al (8). Thus, when the twofold difference in MspI cleavage rate is taken into account, the differences attributable to nuclear accessibility are reduced to fivefold for kidney and liver and negligible for spleen.…”
Section: Resultssupporting
confidence: 92%
“…In consideration of the possibility that the observed differences were due to the ability of MspI to cleave unmethylated DNA more efficiently than methylated DNA, naked genomic DNA from methylated and unmethylated transgenic liver was digested with increasing amounts of MspI under conditions nearly identical to those used with the nuclei. We observed MspI to cleave unmethylated sequences approximately twice as efficiently as methylated sequences (data not shown), in close agreement with the results of Butkus et al (8). Thus, when the twofold difference in MspI cleavage rate is taken into account, the differences attributable to nuclear accessibility are reduced to fivefold for kidney and liver and negligible for spleen.…”
Section: Resultssupporting
confidence: 92%
“…Acclll, Hpall and Mspl contain 5'-CCG-3' within their recognition sequence. The methylation sensitivities of Hpall and Mspl, as reported by Butkus et aL (1987), were evident in Figure 1. Labbe et aL (1988) previously reported that Acclll was able to cut its recognition site if either cytosine was methylated.…”
Section: Discussionmentioning
confidence: 62%
“…The isoschizomeric pair Hpall/Mspl cuts the sequence 5'-C/ CGG-3' but each enzyme differs in its sensitivity to cytosine methylation (Butkus et aL, 1987;McClelland et aL, 1994). Hpall cuts very weakly if the outer C is methylated, but does not cut if the inner C is methylated.…”
Section: Methylation Sensitivity Of Hpall Mspl and Acclllmentioning
confidence: 99%
See 1 more Smart Citation
“…We then tested the ability of a pair of cytosine methylationsensitive isochizomeric endonucleases (HpaII and MspI) to cleave their recognition sequence, CCGG, in the STSV1 genome. Cleavage by HpaII and MspI is inhibited by methylation at the internal and external cytosine residues of the site, respectively (14). All of the CCGG sites in STSV1 DNA were cleaved by HpaII.…”
Section: Vol 79 2005mentioning
confidence: 99%